Impact of Internal Financing on Firms Value among Deposit Money Banks in Nigeria - Ahmad, Ado; Aliyu, Sadiya A. G.; Kaseem, Nafisatu; Frank, Agbdagri (Kashere Journal of Management Sciences, 2024)
This paper is focused on the impact of internal financing on firm`s value among deposit money banks in Nigeria. The identifies internal sources of funds and their effect on firm`s value. The sources include retained profit, sale of assets and reduction or controlling of working capital. Advantages of these sources were also looked into. The study was based on financial report of some selected banks, it was found out that the retained earnings has significant impact on value of DMBs in Nigeria, because it add to the value of the firm and therefore the firms are recommended to finance business internally as it is healthier than external financing which attracts rate of return sometimes at high rate. Retain profit, sale of assets and reduction of working capital improve financial value of firms.